THE IMPACT OF GOVERNMENT SPENDING ON MONEY SUPPLY AND GDP GROWTH IN THE IRAQI ECONOMY FOR THE PERIOD 2003-2023 - Hayder H. Al-Bujabir; Qahtan Lafta Attia Al-Rubaie; Mohammed Shihab Ahmed (Scholars Digest Publishing, 2024)
Government spending is one of the macro variables that play an important and vital role in influencing various economic activities in general, and the money supply and economic growth in particular, as government spending has recently taken noticeable increases resulting from increased responsibility and burden on governments, which leads to a rise in the government role in economic activity, in order to reach the goal of research, which is to know the impact of government spending on both the money supply and economic growth in GDP. Overall, a standard model was built based on the EViews 12 program, two models of joint integration were built using the slow-gap autoregressive model (ARDL), the first is related to the relationship between government spending as a monetary variable and GDP as a real variable as well as government spending and money supply as two monetary variables. It was found that the existence of a relationship of mutual integration between variables as well as the dependence of GDP and money supply at a very high rate on government spending, so the most important recommendation in the research is The need to reduce state interference in economic activity and give an opportunity to the private sector to take its role in increasing the contribution to GDP.